2020
DOI: 10.3126/njog.v15i2.32902
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Peripartum Hysterectomy at a Tertiary Care Hospital: A Five Year Analysis

Abstract: Aims: To analyze the medical records of emergency peripartum hysterectomy in a teaching hospital Methods: A hospital based descriptive cross-sectional study was carried out on emergency peripartum hysterectomy at National Medical College and Teaching Hospital, Birgunj, Nepal from July 2011 to July 2016. Data were collected from the medical record. Results: There were 29 maternal survivors out of 33 cases of emergency peripartum hysterectomy, among which 21 cases were of subtotal and rest 11 had und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Another explanation for this increase rate of hysterectomy in this study might be due to significant linear increase in uterine rupture. This finding relates to that in Nepal, where hysterectomy trend was increasing over the years with majority of cases arising from uterine rupture leading to PPH [37]. With an increase number of cesarean sections unpublished data from Tanzania by Zahra et al, showed that in the ten-year period there was a rise in rate of peripartum hysterectomy from 2008 to 2017 [38].…”
Section: Discussionmentioning
confidence: 53%
“…Another explanation for this increase rate of hysterectomy in this study might be due to significant linear increase in uterine rupture. This finding relates to that in Nepal, where hysterectomy trend was increasing over the years with majority of cases arising from uterine rupture leading to PPH [37]. With an increase number of cesarean sections unpublished data from Tanzania by Zahra et al, showed that in the ten-year period there was a rise in rate of peripartum hysterectomy from 2008 to 2017 [38].…”
Section: Discussionmentioning
confidence: 53%